Seasonal variability in dry matter dynamics and net primary productivity of grassland ecosystem in Kumaun Himalaya - Archana Fartyal; Surendra Singh Bargali; Kiran Bargali (Geology, Ecology, and Landscapes)
Grasslands in the Kumaun Himalayan region, formed largely due to degradation of forests by natural and anthropogenic disturbances, are ecologically significant but poorly studied in terms of dry matter dynamics and net primary productivity. This study compared seasonal biomass and productivity variations in grasslands under two contrasting forest zones (Banj oak and Chir pine). Three permanent plots were established in each zone and within each of these plots 10 quadrats of 1m × 1m were placed randomly on monthly basis. Maximum density, total basal area, diversity and live aboveground biomass were observed during the rainy season, while dead shoot biomass peaked in winter. Aboveground net productivity ranged from 280.96 g m-2 to 394.83 g m-2 for oak and pine zone grassland, respectively. All biomass compartments varied significantly with season, site, and their interaction (p<0.05). High aboveground biomass and productivity during rainy season indicates that precipitation promotes aboveground biomass in grasslands. Oak zone grassland showed lower productivity and nutrient content as compared to pine zone due to greater grazing and human pressure. This study concludes that grassland productivity was directed aboveground during the monsoon season and belowground during post-monsoon season, with environmental and anthropogenic factors driving these patterns. Understanding these dynamics is crucial for managing and conserving Himalayan grassland ecosystems.